Pengaruh Open Suction System terhadap Kolonisasi Staphylococcus aureus pada Pasien dengan Ventilator Mekanik di Ruang Intensive Care Unit (ICU) RSD dr. Soebandi Jember (The Effect of Open Suction System on Staphylococcus aureus Colonization in Patients wi - Rahma Yunita; Rondhianto Rondhianto; Wantiyah Wantiyah (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Patients who are treated using mechanical ventilation is more prone to pnumonia nosocomial infection. It is the highest contributing symptoms to mortality found at the Intensive Care Unit (ICU). The bacteria which accounts for the infection is Staphylococcus aureus. One of the avaliable treatments for preventing the incidence of pneumonia nosocomial infection is using the Open Suction System. This research employed pre-experiment design and was set using the one group pretest-posttest design. The sampling collection technique used in this research was consecutive sampling. The statistical testing employed by this research was the dependent t-test. The result showed that the p value = 0,025 < α and t value = +3,177, indicating that there was significant effect of open suction system on the colonization of Staphylococcus aureus in patients with mechanical ventilation at intensive care unit RSD dr. Soebandi Jember. Open suction system could increase the colonization of Staphylococcus aureus with an average 33,33 CFU/ml. The result of this research helps to provide consideration in fixing the Standard Operating Procedure of open suction system in patients with mechanical ventilation at ICU because open suction system has better capability to prevent pneumonia nosocomial than closed suction system if applied with appropriate procedure Keywords: open suction system, mechanical ventilation, Staphylococcus aureus colonization.